SUSTAINABLE ACCOUNTING PRACTICES IN A VILLAGE-OWNED ENTERPRISE : A TRIPLE BOTTOM LINE CASE STUDY OF CAFE JAMU BUMDES KEPUHANYAR - Noviana, Franciska Diah Ayu; Kusumaningtias, Rohmawati; Samad, Nur Hayati Binti AB (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the implementation of sustainable accounting practices using the Triple Bottom Line framework at Cafe Jamu, a village-owned enterprise (BUMDes) in Kepuhanyar, Mojokerto.Methods: This study uses a qualitative case-study approach based on Geoff Lamberton’s 2000 sustainable accounting framework, which includes five evaluation components: sustainable financial performance, eco-efficiency, ecological sustainability, intragenerational equity, and intergenerational equity. Data collection involved semi-structured interviews, observation, and document analysis. The results were analyzed using the interactive analysis model by Miles, Huberman, and Saldaña. Data validity was maintained through source and method triangulation, with results confirmed by informants.Results: The results indicate that Cafe Jamu has implemented sustainable activities despite the absence of a formal accounting and reporting system. Empirical findings highlight five key areas: sustainable financial performance, eco-efficiency, ecological sustainability, intragenerational equity, and intergenerational equity. These practices are reflected in business stability, effective utilization of available resources, business reliance on local raw materials, community empowerment in the village, and preservation of knowledge about the use of traditional herbal medicines. Based on stakeholder theory, sustainability practices are influenced by local stakeholders’ interests and needs, and legitimacy theory implies that the social legitimacy of BUMDes will be related to the alignment of its operations with the community.Conclusion and suggestion: According to the study’s findings, Café Jamu's sustainable accounting practices are unevenly implemented, with environmental and cultural factors prioritizing distribution, and economic factors. To improve economic performance while upholding community-based sustainability values, it is recommended that the company gradually establish a basic financial and sustainability recording system. Keywords: BUMDes, Sustainable Accounting, Triple Bottom Line, SDGs